Effectivity System of Management Information in Information Tehcnology Center University of Sam Ratulangi Manado. - Kalalo, Intani Kirana; Mandey, Jantje; Pombengi, Jericho (JURNAL ADMINISTRASI PUBLIK, 2015)
ABSTRACT   In accordance with Regulation of the Minister of  Education and Culture of the Republic  of Indonesia on the Organization and Work of Sam Ratulangi University of article 105, paragraph  1, which states that the Information and Communication Technology Unit is a unit of the technical  implementation  in  the  field  of  development  and  management  of  systems  and  information  and  communication technology. And Article 106, namely, Information and Communication Technology  Unit  has  the  tasks  of  system  development  and  management  of  information  and  communication  technology as well as the provision of information and communication technology services.    This study used a qualitative method, data source or informant study of 10 people in the  capture of some elements, such as students 8 people, and Lecturer 2 people. Collecting data using  questionnaires, interviews, and documentation. Based on the research, it can be concluded that the  effectiveness of management information systems at the center of the information technology (PTI)  Sam Ratulangi University, yet effective.    Timeliness, accuracy of information, and human resources must be developed. As well as  the facilities and infrastructure must also be added.   Keywords: effectiveness, management information system